2009 IEEE 70th Vehicular Technology Conference Fall 2009
DOI: 10.1109/vetecf.2009.5378783
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Multilane Roundabout Capacity "Case Study"

Abstract: This paper compares the capacity analysis suggested by the Federal Highway Administration (FHWA) roundabout guidelines with those of the Transportation Research Board (TRB draft report, 2006) and National Highway Cooperative Research Program (NHCRP report 572). The result will be given in term of average control delay time, 95th percentile queue length, and capacity of the critical lane in the critical approach, or the overall approach depending on the method used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…But, at the same time, they have become a controversial point for drivers [24]. Some results presented in previous studies (in the United States and China) showed that drivers do not have enough skills circulating in roundabouts, generating traffic jams in the vicinity [24,15].…”
Section: Problem Approach: Roundaboutmentioning
confidence: 99%
“…But, at the same time, they have become a controversial point for drivers [24]. Some results presented in previous studies (in the United States and China) showed that drivers do not have enough skills circulating in roundabouts, generating traffic jams in the vicinity [24,15].…”
Section: Problem Approach: Roundaboutmentioning
confidence: 99%
“…In the last 20 years, Spanish urban and interurban roads roundabouts have been replacing intersections progressively with the idea of improving traffic flow [12]. However, roundabouts have become one of the most conflicting traffic scenarios [13,14]. In fact, studies [15,16] carried out by the DGT (Spanish Traffic Agency) between 2012 and 2016 concluded that accidents in roundabouts increased by almost 34%, and according to Reference [17], the number of fatal accidents in roundabouts doubled over the same period.…”
Section: Introductionmentioning
confidence: 99%
“…However, at the same time they have become a point of conflict for many drivers (Abaza and Hussein, 2009). Studies (in the U.S and China) have shown that drivers that don't have experience using roundabouts cause traffic jams in the vicinity (Xiaoguang et al, 2004;Abaza and Hussein, 2009;Yu et al, 2009). …”
Section: Introductionmentioning
confidence: 99%